Land use changes and landscape pattern dynamics of a peatland area under diversified human impact: the Grójec Valley (Central Poland) - Glina, Bartłomiej; Sykuła, Marcin; Mendyk, Łukasz (Bulletin of Geography. Physical Geography Series, 2019)
The paper aims to assess the land use changes and the dynamics of the landscape pattern of the Grójec Valley in the scope of diverse anthropogenic impacts. The study site is located in the border of the Koło Basin and Kujawy Lakeland, Central Poland. This area was originally covered with wetlands. Since the beginning of the 20th century it has been influenced by intensive agricultural use, peat extraction and open-pit mining. The research is based on cartographic materials from 1941, 1981 and 2012. The most relevant finding was that in the first study period (1941–1981) the most common changes in land use (transformation of wetlands into grasslands with shrubs) took place. These were caused mainly by a change in hydrological conditions due to drainage for agricultural use (meadows and pastures) and peat extraction. The study confirmed that these land use changes significantly influenced the landscape structure in each of the analysed parameters (patch density and size, edge, shape and diversity metrics).